1996
DOI: 10.21273/jashs.121.5.838
|View full text |Cite
|
Sign up to set email alerts
|

Whole-plant Net CO2 Exchange of Raspberry as Influenced by Air and Root-zone Temperature, CO2 Concentration, Irradiation, and Humidity

Abstract: The influence of irradiance, CO2, and temperature on whole-plant net CO2 exchange rate (NCER) of Rubus idaeus L. `Heritage' micropropagated raspberries was examined. Within the set of environmental conditions examined, irradiation was the most important factor, accounting for 58% of the whole-plant irradiance/CO2 concentration/temperature NCER model variation, followed by CO2 concentration (28… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
22
0
5

Year Published

1998
1998
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 35 publications
5
22
0
5
Order By: Relevance
“…Net photosynthesis in red raspberry is optimal below 25 °C, peaking typically around 17–21 °C (Percival et al . ; Stafne et al . ; Hall & Sobey ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Net photosynthesis in red raspberry is optimal below 25 °C, peaking typically around 17–21 °C (Percival et al . ; Stafne et al . ; Hall & Sobey ).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we evaluated the short-term temperature response of g m in red raspberry (Rubus idaeus L.), an economically important horticultural crop of northern hemisphere origins, which readily adapts to cool temperate climatic conditions (Hall & Sobey 2013). Net photosynthesis in red raspberry is optimal below 25°C, peaking typically around 17-21°C (Percival et al 1996;Stafne et al 2001;Hall & Sobey 2013). We evaluated g m from 20 to 35°C, which is representative of the maximal daytime T leaf differential experienced by raspberry leaves out in the open field on sunny summer days in southern Québec where plants were obtained.…”
Section: Introductionmentioning
confidence: 99%
“…Leaf chlorophyll content of Freeman maple cultivars was reduced by a constant RZT of 34°C compared with 28°C for 32 d (Wilkins et al, 1995). Air temperature and RZT in the range of 15 to 35°C influenced CO 2 assimilation in Rubus idaeus L. 'Heritage', with maximum rates occurring at an air temperature/RZT of 17/25°C (Percival et al, 1996). High RZT in Prunus mira Koehne (smoothpit peach) seedlings decreased leaf water content and decreased photosynthesis (Hao et al, 2012).…”
Section: Indirect Injurymentioning
confidence: 99%
“…A. crenata is a very slow-growing shade-tolerant plant (Kitajima et al 2006), and growth respiration may be low relative to maintenance respiration. Previous studies have found low Q 10 values of whole-plant respiration, often lower than 1.5 (Percival et al 1996;Frantz et al 2004), but in these other species, growth respiration was proportionally higher than in A. crenata. A. crenata grows in the understorey of warm to temperate evergreen forests in its native environment in Japan and also in Florida (Kitajima et al 2006).…”
Section: Plant Carbohydrates and Controls Over Respiration Ratesmentioning
confidence: 54%